INTERAKSI SIMBOLIK PADA ORGANISASI PERSIT KARTIKA CHANDRA KIRANA CABANG XVI BATALYON ARHANUD 13 - Hesty Fazar Afriani (2022)
Humans communicate daily through the interpretation of the meaning of the symbols contained in a message. Humans are interdependent in people's lives, so that in understanding how humans interact with each other they create a symbolic world. This study aims to find out how the symbolic interactionism process in the Persit Kartika Chandra Kirana Cabang XVI organization uses symbolic interaction theory and 3 main concepts, mind, self, and society in which symbols of self-identity, speech, calling, gestures can be seen when the interaction between fellow members of Persit takes place. The type of research used is qualitative with phenomenological methods and the use of primary and secondary data sources. The sampling technique was carried out by purposive sampling. Researchers used four stages of data analysis according to Miles & Huberman, namely data collection, data reduction, data presentation, and data conclusion. The results of this study were found the use of speech and the way of calling in Persit based on the hierarchy of each member of Persit based on the husband's rank of an Army soldier. The rules of clothing, gestures, rules of behavior, and verbal symbols in Persit symbolize the meaning that Persit is an organization that has strict rules and regulations that must be carried out by all members of Persit. Keywords: Symbolic Interaction, Hierarchy, Military Culture